IMPLEMENTATION OF INDIVIDUAL COUNSELING SERVICES TO BUILD STUDENTS' CONFIDENCE CLASS XI AT MAN 3 LANGKAT - Rahmah, Mukhliza (Faculty of Tarbiyah nad Teacher Training, 2023)
This study aims to find out how the condition of student self-confidence, the implementation of individual counseling is given in building student self-confidence and how the planning is carried out by individual counseling teachers in building student self-confidence at MAN 3 Langkat.This study uses a type of qualitative research, with a case study design. The participants in this study were guidance and counseling teachers and 11 students. Data collection was carried out using observation, documentation and interview techniques. The data analysis technique uses data reduction, data presentation, and drawing conclusions. The results of this study revealed that the condition of the students' self-confidence at MAN 3 Langkat was quite good, but even so there were still some students who were not confident in their abilities, felt pessimistic that the goals they wanted would not be achieved, and lacked motivation. people around.The implementation of individual counseling in schools in building students' self-confidence at school is considered successful, the counseling teacher uses several stages including, which allows students to be more flexible in conveying the feelings they want to convey. Obstacles faced in the implementation of individual counseling services include obstacles in terms of determining the schedule for the implementation of services, then in terms of places that make the implementation of services carried out quite well but are still less effective because there is no special place provided.